Sperm cryopreservation of transgender individuals: trends and findings in the past decade. (9th August 2018) - Li, K.; Rodriguez, D.; Gabrielsen, J. S.; Centola, G. M.; Tanrikut, C.
Abstract: Objectives: Awareness and acceptance of transgenderism have increased in the last two decades. There is limited literature regarding the incidence and semen characteristics of transwomen banking spermatozoa. We sought to assess the incidence of sperm cryopreservation of transgender individuals compared with the cisgender population in the last 10 years. Semen parameters were also compared between the two groups. Materials and methods: We performed a retrospective analysis of sperm cryopreservation performed at a single center from 2006 through 2016. Using available data on indications for banking and prior hormonal therapy status, we isolated healthy transgender and cisgender cohorts for semen parameter comparison. Linear regression was used to compare the incidence trends. Semen parameters were compared using the generalized estimating equations method. The rates of semen parameter abnormality of each group were compared using chi‐square test. Semen parameter abnormalities were defined using WHO 2010 reference values. Results: We analyzed 194 transgender samples and 2327 cisgender samples for a total of 84 unique transgender sperm bankers and 1398 unique cisgender sperm bankers. The number of transgender sperm bankers increased relative to cisgender sperm bankers from 2006 to 2016. Following exclusion of cisgender sperm bankers with health issues that might impact semen quality and transgender sperm bankers with known prior hormonal therapy, we compared the semen parameters of 141 healthy cisgender sperm bankers and 78 healthy transgender sperm bankers. The transgender sperm bankers demonstrated lower sperm concentration, total motile sperm count, and post‐thaw sperm parameters. The transgender sperm bankers also demonstrated a higher incidence of oligozoospermia. Conclusions: This is the largest report to date on the incidence of transgender sperm cryopreservation and comparison of semen characteristics with cisgender sperm bankers. The data reveal an increased incidence of transgender sperm banking as well as poorer semen parameters of transgender individuals compared with cisgender controls.